2003
DOI: 10.1046/j.1460-9568.2003.02614.x
|View full text |Cite
|
Sign up to set email alerts
|

The transient depression of hippocampal CA1 LTP induced by chronic intermittent ethanol exposure is associated with an inhibition of the MAP kinase pathway

Abstract: Using electrophysiological and biochemical approaches, we investigated the effects of chronic, intermittent ethanol (CIE) treatment on activation of the mitogen activated protein kinase (MAPK), also known as extracellular signal regulated protein kinase 1 and 2. In hippocampal slices taken from control rats, brief high-frequency stimulation to Schaffer collateral fibers induced a large post-tetanic potentiation (PTP) in the CA1 region that decayed to stable long-term potentiation (LTP) of field extracellular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 45 publications
2
46
1
Order By: Relevance
“…However, in vivo exposure data are more consistent, revealing an ethanol-induced decrease in npg ERK activation [13][14][15] , except in the report from Bachtell et al [32] . Our data are in agreement with previous reports in which chronic ethanol exposure in vivo decreased ERK phosphorylation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, in vivo exposure data are more consistent, revealing an ethanol-induced decrease in npg ERK activation [13][14][15] , except in the report from Bachtell et al [32] . Our data are in agreement with previous reports in which chronic ethanol exposure in vivo decreased ERK phosphorylation.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, several studies [13][14][15] have suggested that the ERK signaling pathway is one of the targets of ethanol. For example, acute application of ethanol has been shown to attenuate MAPK activation in cultured cortical neurons and in mouse cerebral cortex in vivo [13] .…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that target-dependent modulation of neurotransmitter release from Helix presynaptic terminals crucially depends on MAPK/Erk activation . Although MAPK/Erk activity does not appear to be required for short-term heterosynaptic facilitation induced by serotonin at Aplysia sensorimotor synapses Purcell et al, 2003;Phares and Byrne, 2005), other studies in invertebrates show that modulation of short-and long-term synaptic plasticity paradigms is mediated by MAPK/Erk (Tancredi et al, 2000;Chin et al, 2002;Roberto et al, 2003;Giachello et al, 2008;Khoutorsky and Spira, 2009). An involvement of MAPK/Erk in short-term plasticity is also supported by studies in transgenic mice that express a constitutively active form of H-Ras, which exhibit an enhancement of paired-pulse facilitation and long-term potentiation that is dependent on MAPK/Erk activation (Kushner et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Binge ethanol exposure also results in necrotic cell death and neurodegeneration in the hippocampus (Obernier et al 2002;Hamelink et al 2005). Moreover, evidence from studies examining the effects of ethanol on hippocampal plasticity suggests that chronic ethanol inhibits hippocampal LTP (Durand and Carlen 1984;Tremwel and Hunter 1994;Roberto et al 2002Roberto et al , 2003, which may underlie chronic ethanol-induced deficits in hippocampus-dependent learning and memory. Ethanol inhibition of LTP may result from decreased excitability of hippocampal neurons due to blockage of NMDA receptors, specifically NR1/ NR2A or NR1/NR2B subtypes (Hoffman et al 1989;Lovinger et al 1989;Schummers and Browning 2001;Izumi et al 2005; for review, see Allgaier 2002) as well as activation of inhibitory GABA A receptors (Allan and Harris 1986;Aguayo 1990;Reynolds et al 1992;Schummers and Browning 2001).…”
Section: Effects Of Prolonged Alcohol Exposure On Hippocampal Functionmentioning
confidence: 99%
“…Ethanol inhibition of LTP may result from decreased excitability of hippocampal neurons due to blockage of NMDA receptors, specifically NR1/ NR2A or NR1/NR2B subtypes (Hoffman et al 1989;Lovinger et al 1989;Schummers and Browning 2001;Izumi et al 2005; for review, see Allgaier 2002) as well as activation of inhibitory GABA A receptors (Allan and Harris 1986;Aguayo 1990;Reynolds et al 1992;Schummers and Browning 2001). In addition to alterations of NMDA and GABA receptor function in the hippocampus, ethanol-induced suppression of hippocampal LTP has been associated with the inhibition of MAPK signaling (Sanna et al 2002;Roberto et al 2003;Chandler and Sutton 2005;Wang et al 2012). Roberto et al (2003) showed that following chronic intermittent ethanol treatment, both LTP and ERK1/2 activation were reduced in the hippocampus.…”
Section: Effects Of Prolonged Alcohol Exposure On Hippocampal Functionmentioning
confidence: 99%